2015
DOI: 10.1038/srep10264
|View full text |Cite
|
Sign up to set email alerts
|

Spheroidal carbonaceous particles are a defining stratigraphic marker for the Anthropocene

Abstract: There has been recent debate over stratigraphic markers used to demarcate the Anthropocene from the Holocene Epoch. However, many of the proposed markers are found only in limited areas of the world or do not reflect human impacts on the environment. Here we show that spheroidal carbonaceous particles (SCPs), a distinct form of black carbon produced from burning fossil fuels in energy production and heavy industry, provide unambiguous stratigraphic markers of the human activities that have rapidly changed plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 24 publications
7
38
0
2
Order By: Relevance
“…Importantly, a more recent date is also supported by a publication (poster) using 1976 as the SCP peak with Evans listed as a co-author (Collier et al, 2016). Therefore, the selection of 1975 as the peak age, which sits comfortably with the 1977 ± 5 estimate given by Swindles et al (2015), probably had very little impact on the findings of our study. Figure 1 clearly shows that the peak shape is very similar for all three sites.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Importantly, a more recent date is also supported by a publication (poster) using 1976 as the SCP peak with Evans listed as a co-author (Collier et al, 2016). Therefore, the selection of 1975 as the peak age, which sits comfortably with the 1977 ± 5 estimate given by Swindles et al (2015), probably had very little impact on the findings of our study. Figure 1 clearly shows that the peak shape is very similar for all three sites.…”
supporting
confidence: 82%
“…Therefore, the selection of 1975 as the peak age, which sits comfortably with the 1977 ± 5 estimate given by Swindles et al (2015), probably had very little impact on the findings of our study. SCP counts shown in Swindles et al, 2015). However, we agree that our study would have benefited from additional dating methods, which we stated within the paper.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…3). This is linked with the appearance of other chronomarkers, e.g., spheroidal carbonaceous particles (SCP), whose numbers have rapidly increased everywhere after the second world war19. SAP are a typical inorganic, glassy component of fly ash generated during industrial coal combustion2122232425 and are found even in regions located far from industrial centres, e.g., Greenland (Summit area)26 and the glaciers of Tianshan27.…”
Section: Resultsmentioning
confidence: 99%
“…1)141516. Furthermore, no existing studies identify the recently proposed Anthropocene period, the period in which human activity dramatically altered all earth systems171819. Here, we provide a first high-resolution record of dust flux as evidence for geochemical anomalies of both anthropogenic- and natural origin in the Mukhrino peatland in Western Siberia (Fig.…”
mentioning
confidence: 76%